Surgical Treatments for Lumbar Spine Diseases (TLIF vs. Other Surgical Techniques): A Systematic Review and Meta-Analysis - Wasinpongwanich, Kanthika; Nopsopon, Tanawin; Pongpirul, Krit (Frontiers in Surgery, 2022)
Objective: To compare fusion rate, clinical outcomes, complications among Transforaminal Lumbar Interbody Fusion (TLIF), and other techniques for lumbar spine diseases. Design: Systematic review and meta-analysis. Data sources: PubMed, Embase, Scopus, Web of Science, and CENTRAL databases were searched from January 2013 through December 2019. Eligibility criteria for selecting studies: Randomized controlled trials (RCTs) comparing lumbar interbody fusion with posterolateral fusion and/or other lumbar interbody fusion were included for the review. Data Extraction and Synthesis: Two independent reviewers extracted relevant data and assessed the risk of bias. Meta-analysis was done using a random-effects model. Pooled risk ratio (RR) or mean difference (MD) with a 95% confidence interval of fusion rate, clinical outcomes, and complications in TLIF and other techniques for lumbar spinal diseases. Results: Of 3,682 potential studies, 15 RCTs (915 patients) were included in the meta-analysis. Compared to other surgical techniques, TLIF had slightly lower fusion rate (RR=0.84 [95% CI 0.72, 0.97], p=0.02, I2=0.0%) at 1-year follow-up while there was no difference on fusion rate at 2-year follow up (RR=1.06 [95% CI 0.96, 1.18], p=0.27, I2=69.0%). The estimated risk ratio of total adverse events (RR=0.90 [95% CI 0.59, 1.38], p=0.63, I2=0.0%) was similar to no fusion, PLF, PLIF, XLIF group and revision rate (RR=0.78 [95%CI 0.34, 1.79], p=0.56, I2=39.0%) was similar to PLF and XLIF group. TLIF had approximately half an hour more operative time than other techniques (No fusion, ALIF, PLF, PLIF, XLIF) (MD=31.88 [95% CI 5.33, 58.44], p=0.02, I2=92.0%). There was no significant difference between TLIF and other techniques in terms of the blood loss (No fusion, PLIF, PLF), and clinical outcomes (PLF). Conclusions: Besides fusion rate at 1-year follow-up and operative time, TLIF has a similar fusion rate, clinical outcomes, parameters concerning operation and complications to no fusion, posterolateral fusion, and other interbody fusion (PLIF, ALIF, XLIF).